Exposure assessment of polycyclic aromatic hydrocarbons from the consumption of processed cowhide (Wele), a West African delicacy - Acquah-Baidoo, D.; Affrifah, N.S.; Afoakwa, E.O.; Saalia, F.K. (Scientific African, 2023)
This study describes the occurrence and profile of eight polycyclic aromatic hydrocarbons (PAHs) in fresh and cooked processed cowhide (wele) singed with different fuels. It also assessed the health risks associated with the consumption of this popular delicacy. The 8PAHs were all detected in the wele samples singed with scrap tires, whereas 5 and 3 carcinogenic PAHs were detected in the firewood and liquefied petroleum gas (LPG) singed wele, respectively. For each of the specific PAH detected, the contents in the wele samples were generally ranked as scrap tires > firewood > LPG. The average concentrations of benzo[a]pyrene for cooked wele samples were 2.75 ng g−1(firewood) and 22.85 ng g−1(scrap tires); exceeding the 2.0 ng g−1 European Commission regulation max imum levels (MLs) for smoked products. For the carcinogenic risk exposure assessment, the dietary intake based on benzo[a]pyrene equivalents was estimated as 777.06 ng g−1 day (scrap tires), 101.52 ng g−1 day (firewood) and 9.45 ng g−1 day (LPG). The probable cancer risk estimated considering the consumption frequency and quantity of wele for an average adult consumer was highest in the population exposed to wele singed with scrap tires (3.11×10−5).
Research Article